Phase formation and electrical properties of lead-free bismuth sodium titanate-potassium niobate ceramics - Pengpat K. (2014)
Lead-free piezoelectric ceramics in the (1-x)(Bi0.5Na0.5)TiO3- xKNbO3:(1-x)BNT-xKN system, were prepared by a two-step mixed oxide method and investigated over the entire compositional range where x = 0.0 to 1.0. Difficulty in preparing dense ceramics was encountered where the content of KN is greater than 50 mol%. XRD results showed that most of the BNT-KN ceramics contain ferroelectric perovskite phase with a mixture of rhombohedral and orthorhombic symmetries. The dielectric constant at room temperature (εr) was found to increase with increasing KN. The maximum piezoelectric coefficient (d33) of about 170 pC/N was obtained in the 0.9BNT-0.1KN sample. The broadness of the dielectric constant peak increased with increasing KN content, especially that of the 0.7BNT-0.3KN ceramic which exhibited a very broad curve over a wide temperature range. This may be useful in the development of lead-free capacitors. © 2007 Elsevier B.V. All rights reserved.